Alterations of protein expression in conditions of copper-deprivation for Paracoccidioides lutzii in the presence of extracellular matrix components - Oliveira, Haroldo Cesar de [UNESP]; Silva, Julhiany de Fatima da [UNESP]; Matsumoto, Marcelo Teruyuki [UNESP]; Marcos, Caroline Maria [UNESP]; Silva, Roberta Peres da [UNESP]; Moraes da Silva, Rosangela Aparecida [UNESP]; Veneziano Labate, Monica Teresa; Labate, Carlos Alberto; Fusco Almeida, Ana Marisa [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Biomed Central Ltd, 2014)
Background: Paracoccidioides spp is a fungi genus and the agent of paracoccidioidomycosis. The strategies of infection used by these pathogens involve the expression of proteins related to adaptation to the host, particularly regarding the uptake of micronutrients. This study analyzed the adhesion of Paracoccidioides lutzii during conditions of copper (Cu) and iron (Fe) deprivation, while also evaluating the proteins expressed in conditions of Cu depletion in the presence of four extracellular matrix (ECM) components (laminin, fibronectin and types I and IV collagen).Results: We cultured the P. lutzii in a chemically defined media without Cu and Fe. The fungus was then placed in contact with different ECM components and adhesion was evaluated. A significant increase in binding to all ECM components was observed when the fungus was cultured without Cu; which might be related to some adhesins expression. A proteomic assay was developed and revealed 39 proteins expressed that are involved in processes such as virulence, protein synthesis, metabolism, energy, transcription, transport, stress response and the cell cycle when the fungus was interacting with the ECM components. The up-regulated expression of two important adhesins, enolase and 14-3-3, was observed at the fungal cell wall during the interaction with the ECM components, indicating the role of these proteins in the Paracoccidioides-host interaction.Conclusions: This study is important for determining prospective proteins that may be involved in the interaction of Paracoccidioides with a host. Understanding the adaptive response to different growth conditions, elucidating the processes of adhesion and cell invasion, and identifying the proteins that are differentially expressed during the fungus-host interaction may help elucidate mechanisms used for survival and growth of Paracoccidioides in various human tissues.
Keywords: Paracoccidioides spp; Copper; Adhesion; Protein expression; Paracoccidioidomycosis